The influence of mechanical effects on the damages of broiler breeder hatching eggs and hatchability results different types of egg trays - Torma, Tímea; Kovácsné Gaál, Katalin (Animal welfare, Ethology and Housing Systems (AWETH), 2019)
It is more and more common practice to transport hatching eggs to a hatchery on a plastic or setter tray. However, we need to be aware of the scale of damage can be done to the hatching eggs and hatchability. Piezo sensors and data loggers available nowadays make it possible to monitor the mechanical impact. The aim of the experiments to express in numbers scale of mechanical impacts and present different scale of impacts effect on hatchability. The authors investigated the effect of mechanical impact modelling on eggs in different types of trays. RSM(x, y, z) (root mean square of the resultant acceleration) and RSS (square root of the sum of the squares of the resultant acceleration in all three direction) were calculated from logger data to determine mechanical effect, which can be used to determine the type and direction of impact and to express in number. With dead in shell post mortem technique the day of mortality and different symptoms were determined. The mechanical impact of 10 to 30 Hz for 10 minutes and a 20 Hz exposure of 5 minutes on a plastic tray significantly reduced hatchability (P
Keywords: mechanical effects; monitoring; hatchability results; egg tray types